Influence of Sedation on the Detection Rate of Early Cancer and Precancerous Lesions During Diagnostic Upper Gastrointestinal Endoscopies: A Multicenter Retrospective Study. (3rd June 2021) - Zhou, Jiawei; Li, Zhen; Ji, Rui; Wang, Peizhu; Zhang, Aijun; Wu, Kangkang; Liu, Chengxia; Niu, Qiong; Chu, Yanliu; Su, Xiufeng; Zuo, Xiuli; Li, Yanqing
Abstract : INTRODUCTION: The influence of sedation on the endoscopic detection rate of upper gastrointestinal (UGI) early cancer (EC) and precancerous lesions, including high-grade intraepithelial neoplasia (HGIN) and low-grade intraepithelial neoplasia, has not been assessed. The aim of this research is to assess whether the use of sedation can help improve the detection rate of UGI EC and precancerous lesions. The second objective is to evaluate its potential influencing factors. METHODS: The study includes 432, 202 patients from a multicenter database from January 2012 to July 2019. Information on endoscopic findings and histology biopsies was obtained from endoscopy quality-control system. Associations of sedation with the detection rate of EC and precancerous lesions were assessed. RESULTS: The sedation group has a higher detection rate of UGI EC and HGIN compared with the no-sedation group, whereas the detection rate of low-grade intraepithelial neoplasia was similar between the 2 groups. There were more cases examined by using staining, image enhancement, or magnifying techniques in the sedation group ( P < 0.001). And, the mean observation time was also longer in the sedation group ( P < 0.001). The type 0-IIb esophageal HGIN and EC cases were significantly increased in the sedation group. No significant difference was detected on lesion subtypes for gastric HGIN and EC according to the Paris classification. More gastric HGIN and EC were detected at gastric body in the sedation group ( P = 0.001). DISCUSSION: Sedation may improve the endoscopic detection rate of EC and HGIN in the UGI tract probably through enhancing the use of accessary endoscopic techniques, prolonging observation time, and taking more biopsies in different locations (see Visual Abstract, Supplementary Digital Content 2, http://links.lww.com/AJG/B926 ).